Adult Onset Stills Disease- “A Need for Early Diagnosis and Detection of Systemic Score” - Ali, Rubaina; Kumar, Javvaji Sai; Ganesh, Patchigolla (Indian Journal of Pharmacy Practice)
AOSD (adult onset stills disease) is a rare systemic inflammatory disorder of unknown etiology, which is typically characterized by a clinical triad (a high spiking fever, {an evanescent, nonpruritic, macular and salmon coloured rash} and arthritis) and a biological triad (hyperferritinemia, hyperleucocytosis with neutrophilia and abnormal liver function test). We present a case of an adult onset stills disease in a 47 years male patient with presenting complaints of fever, polyarthralgias, cough, pus discharge from nails and lab abnormalities (including anemia, hyperferritinemia and abnormal liver function test). The patient was also complicated with pneumonia. The patient had a past history of herpes oral ulcer and colitis (caused by cytomegalovirus) which was excluded during the diagnosis (made based on yamaguchi criteria) as the patient had the complaints for a long period. The systemic score in our patient was found to be 8, therefore a systemic score of greater than 7 indicates a high risk of mortality. Early detection of systemic score and understanding the clinical presentation of AOSD could be helpful in deciding the therapy and may help to reduce the risk of mortality by improving patient condition. Here we present a case in which the patient was exhibiting clinical presentations of AOSD from a long period of time but was not evaluated, when the condition got worsened the disease was ruled out and started with glucocorticoids but the patient did not respond to the therapy despite of adding 2 corticosteroids and also the TOCILIZUMAB, it was too late as the patient developed complications associated with AOSD such as, the patient complicated with pneumonia and hypotension, contributing to AKI and refractory shock. Development of refractory shock and multiorgan dysfunction led to death.
Keywords: Adult onset stills disease; Yamaguchi criteria; Hyperferritinemia; Systemic score; Pneumonia; Corticosteroid; Tocilizumab.